Peranan Kejaksaan sebagai Dominus Litis dalam Menuntut Lepas Terdakwa terhadap Perkara Tindak Pidana Penganiayaan dalam Perspektif Hukum Pidana - Lyestie Marlya Anggrainy; Murshal Senjaya (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The development of Indonesia’s criminal justice system positions the Public Prosecutor as dominus litis, holding exclusive authority to control prosecution, including filing for dismissal (ontslag van alle rechtsvervolging) to achieve substantive justice. This study examines the legal impact and decision-making mechanism of the Public Prosecutor in assault cases, particularly in educational contexts. Drawing on theories of substantive justice, law enforcement, utility, and Pancasila principles along with the 1945 Constitution, the research concludes that dominus litis authority enables responsible dismissal of cases (as in Decision No. 104/Pid.Sus/2024/PN Adl), preventing over-criminalization of teachers, saving judicial resources, and realizing a humane and proportional restorative justice.